Bridging Islamic Banking Ethics and Practice Through Digital Financial Innovation Technologies - Nurfitri Harkunti Kemala Hayati; Syadila Syahrul (Pattimura Proceeding, 2026)
This article explores how technology-innovation can enhance the ethics of Islamic banking (IB) and help to promote sustainable business. Incorporating both theoretical and analytical reasoning, this study combines the literature on IB ethics, fintech innovation, and sustainability frames. By drawing from existing empirical studies, this paper demonstrates how technology innovations like AI, blockchain and digital banking can enhance the Shariah governance aspect and ethical financial practices when taken holistically. The findings indicate that digitization provides strong potential to close the practical gap between Islamic banking and its ethical ideals. Blockchain technology enables monitoring and can mitigate information asymmetry, enhance transparency in profit-and-loss sharing which help to uphold Shariah compliance. digital could support sharia boards, islamic banks and regulators to enhance sustainability reporting, operational efficiency and compliance. This paper provides a new line of sight, which highlights digitization as an enabler for ethical and sustainable Islamic finance by relating the Islamic ethics to digital transformation and environmental commitment.